Evidence of a Relationship Between Mental Rotation Skills and Performance in a 3D Puzzle Game - VanMeerten, Nicolaas; Varma, Keisha; Gravelle, Matthew; Miller, Nickolas; Kraikul, Evva; Fatemi, Farzan (Frontiers in Education, 2019)
Spatial reasoning is an ability that people utilize on a daily basis, that has also been linked to performance in Science, Technology, Engineering, and Mathematics (STEM) fields. However, there are very few widely available opportunities to train spatial reasoning skills that have been proven to be effective tools. As a first step in the validation process, this study sought to establish whether performance on a measure of intrinsic and dynamic spatial reasoning ability was related to performance within Optica, a mobile puzzle game. To investigate this relationship, 168 middle school students participated in a within-subjects study over three days. The results of this study have been promising, as our analysis indicated that there was a significant relationship between the number of levels completed in Optica and score on the Purdue Spatial Visualization Test - Revised: Visualization of Rotations (Revised PSVT: R).